Sistem Informasi Kesehatan Dan Telemedicine: Narrative Review - Yulita Sirinti Pongtambing; Eliyah A M Sampetoding; Esther Sanda Manapa (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
HIS has a major role in managing health data and information applied through Electronic Medical Records (EMR). EMR facilitates the analysis of health data in patients, decision-making by health care providers, disease mapping, helps identify disease patterns, and maps the spread of the disease. HIS supports the creation of telemedicine services through the concept of telemedicine. This study uses the Narrative Literature Review (NLR) method on the concepts of Health Information Systems (HIS) and Telemedicine. Integrating HIS and Telemedicine provides promising opportunities for healthcare improvement, offering data accessibility, and efficient remote consultation. However, addressing privacy, security, infrastructure, and regulatory challenges is critical to the successful implementation of such integrations. Collaborative efforts between healthcare providers, policymakers, and technology developers are critical to ensuring the ethical and effective implementation of integrated systems.